Role of spinal cord glutamate transporter during normal sensory transmission and pathological pain states - Stephens Robert L; Gu Jianguo; Tao Yuan-Xiang (SAGE Publishing, 2005)
Abstract Glutamate is a neurotransmitter critical for spinal excitatory synaptic transmission and for generation and maintenance of spinal states of pain hypersensitivity via activation of glutamate receptors. Understanding the regulation of synaptically and non-synaptically released glutamate associated with pathological pain is important in exploring novel molecular mechanisms and developing therapeutic strategies of pathological pain. The glutamate transporter system is the primary mechanism for the inactivation of synaptically released glutamate and the maintenance of glutamate homeostasis. Recent studies demonstrated that spinal glutamate transporter inhibition relieved pathological pain, suggesting that the spinal glutamate transporter might serve as a therapeutic target for treatment of pathological pain. However, the exact function of glutamate transporter in pathological pain is not completely understood. This report will review the evidence for the role of the spinal glutamate transporter during normal sensory transmission and pathological pain conditions and discuss potential mechanisms by which spinal glutamate transporter is involved in pathological pain.